Optimal control of structures under earthquake excitation based on the colonial competitive algorithm. (15th October 2012) - Amini, Fereidoun; Bagheri, Abdollah
SUMMARY The active control of engineering structures is one of the best methods to reduce structural responses under seismic excitation for the best performance of structures. This study presents an effective approach for the optimal control of structures under strong ground motion using the colonial competitive algorithm. The colonial competitive algorithm was developed over the last few years in an attempt to overcome the inherent limitations of traditional optimize method. The colonial competitive algorithm has been applied due to its ideal performance in optimal control problem. The effectiveness and performance of the proposed method have been investigated through two numerical examples for the response control of earthquake‐excited structures. The obtained results have been compared with the Linear Quadratic Regulator (LQR) control algorithm, and the performance of the proposed control approach has been found to be better than the LQR controller. Copyright © 2012 John Wiley & Sons, Ltd.